2021
DOI: 10.3389/fsufs.2020.616757
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Consortium Interacts With Different Varieties of Maize, Promotes the Plant Growth, and Reduces the Application of Chemical Fertilizer Under Field Conditions

Abstract: The success of beneficial bacteria in improving the crop growth and yield depends on an adequate plant-bacteria interaction. In this work, the capability of Azospirillium brasilense Sp7, Pseudomonas putida KT2440, Acinetobacter sp. EMM02, and Sphingomonas sp. OF178A to interact with six maize varieties was evaluated by both single-bacterium application and consortium application. The bacterial consortium efficiently colonized the rhizosphere of the autochthonous yellow and H48 hybrid varieties. Bacterial colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…Direct mechanism of PGPR include biofertilization, root stimulation, rhizoremediation, and plant stress control, while antibiosis, induction of systemic resistance and competition for nutrients are the indirect mechanisms of PGPR [32]. It has been shown that, inoculation of beneficial bacteria are able to reduce the use of fertilizer and is a cost effective initiative in reducing the use of agrochemicals [33][34][35]. PGPR such as Burkholderia sp.…”
Section: Bacteriamentioning
confidence: 99%
“…Direct mechanism of PGPR include biofertilization, root stimulation, rhizoremediation, and plant stress control, while antibiosis, induction of systemic resistance and competition for nutrients are the indirect mechanisms of PGPR [32]. It has been shown that, inoculation of beneficial bacteria are able to reduce the use of fertilizer and is a cost effective initiative in reducing the use of agrochemicals [33][34][35]. PGPR such as Burkholderia sp.…”
Section: Bacteriamentioning
confidence: 99%
“…MN-54, Enterobacter, and P. fluorescens 1) as bacterial consortia. In recent years, the co-inoculation of bacterial strains in the same plant has been well reported to stimulate crop growth and development compared to the inoculation of individual bacteria (Mpanga et al 2019;Molina-Romero et al 2021). The functional associative symbiosis in consortium formulations is the key to achieve the beneficial effects of consortia on inoculated plants (Drogue et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among bacteria, actinobacteria are Gram-positive, filamentous bacteria that help in plant growth promotion by increasing the area available for absorption and solubilization of phosphate and by organic recycling, and can also serve as bio-inoculants. Soil actinobacteria release certain chemical compounds that promote plant growth ( Molina-Romero et al., 2021 ; Santoyo et al., 2021 ; Mitra et al., 2022 ; Tsegaye et al., 2022 ). Some research has concluded that microbial combinations are more beneficial than their individual inoculations.…”
Section: Introductionmentioning
confidence: 99%